Cycloadditions of Sugar‐Derived Nitrones Targeting Polyhydroxylated Indolizidines. Issue 8 (17th February 2016) - Martella, Daniele; D'Adamio, Giampiero; Parmeggiani, Camilla; Cardona, Francesca; Moreno‐Clavijo, Elena; Robina, Inmaculada; Goti, Andrea
Abstract: The 1, 3 dipolar cycloaddition reactions of three pentose‐derived pyrroline N ‐oxides with mono‐ and disubstituted alkenes are reported. A strong dependence of the diastereoselectivity of the cycloadditions on the relative configuration of the nitrone stereocentres was observed. Further transformation of the reaction products allowed the synthesis of four new tetrahydroxylated indolizidines. Their activity as glycosidase inhibitors was evaluated against a panel of commercially available glycosidases. The specificity of inhibitory activity against amyloglucosidase and α‐mannosidases depends on the configuration at C‐2 of the indolizidine moiety. Abstract : Sugar‐derived nitrones undergo 1, 3‐dipolar cycloaddition reactions with different dipolarophiles. The diastereoselectivity was dependent on the configuration of the nitrone stereocentres. Some of the cycloadducts were transformed into tetrahydroxylated indolizidines, which were then tested as glycosidase inhibitors.